2012
DOI: 10.1105/tpc.112.106120
|View full text |Cite
|
Sign up to set email alerts
|

WRINKLED Transcription Factors Orchestrate Tissue-Specific Regulation of Fatty Acid Biosynthesis in Arabidopsis  

Abstract: Acyl lipids are essential constituents of all cells, but acyl chain requirements vary greatly and depend on the cell type considered. This implies a tight regulation of fatty acid production so that supply fits demand. Isolation of the Arabidopsis thaliana WRINKLED1 (WRI1) transcription factor established the importance of transcriptional regulation for modulating the rate of acyl chain production. Here, we report the isolation of two additional regulators of the fatty acid biosynthetic pathway, WRI3 and WRI4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
229
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(243 citation statements)
references
References 47 publications
13
229
0
1
Order By: Relevance
“…3). This finding is consistent with other studies that suggest that WRI1 is not a significant regulator of DGAT1 expression (Baud et al, 2007;To et al, 2012).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3). This finding is consistent with other studies that suggest that WRI1 is not a significant regulator of DGAT1 expression (Baud et al, 2007;To et al, 2012).…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have shown that overexpression of the WRI1 transcription factor activates the expression of multiple genes associated with lower glycolysis and fatty acid synthesis (Baud et al, 2007;To et al, 2012) and can enhance oil content in seeds of Arabidopsis (Cernac and Benning, 2004). However, WRI1 has little influence over the expression of genes involved in TAG assembly and packaging (Baud et al, 2007;To et al, 2012). The key enzyme responsible for TAG assembly is encoded by DGAT1 (Katavic et al, 1995;Zhang et al, 2009), and overexpression of this gene can also enhance seed oil content (Jako et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that overall metabolic changes were mostly restricted to total fatty acid contents also indicates that the function of BPM proteins in seeds is strongly connected with WRI1 activity. In this context, it is of note that WRI1 has very recently been described as part of a small gene family with a total of four members in Arabidopsis (To et al, 2012). Although WRI1 is the primary member that regulates fatty acid biosynthesis in seeds, the other members also contribute to this pathway, but they do so in other tissues (To et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One example is where a mutation of the PKL (PICKLE) gene led to the upregulation of a variety of transcription factor genes involved in embryo development and the induction of lipid droplet formation in leaf cells (Ogas et al, 1997). Other examples have focused on one of the downstream transcription factor genes from PKL called WRI1 (WRINKLED1) which is involved in the upregulation of parts of the glycolysis and fatty acid biosynthesis pathways that generate the acyl components required for TAG assembly and accumulation (Ma et al, 2013;To et al, 2012).…”
Section: Accumulating Storage Oil In Non-seed/fruit Tissuesmentioning
confidence: 99%